Emerging Issues in the Global Economy 2017 International Economics Conference in Sibiu (IECS) (Springer Proceedings in Business and Economics,, 2018)
This proceedings volume provides current research on emerging issues in business, economics and finance in the global economy with particular emphasis on Eastern Europe. Featuring selected papers from the 2017 International Economics Conference in Sibiu (IECS) organized by the Lucian Blaga University of Sibiu, Romania, the contributing chapters consider new business models, theories, practices and instruments from advanced and emerging economies in the context of recent global trends. After over 20 years of increasing openness and liberation of the world economy, recent events in regions such as Europe, USA and Asia have created challenges to the idea of globalization and integration. There is a delay between the real-world economic changes and the reflection of such changes in the economic research literature. The 2017 IECS conference and the enclosed papers aim to fill this gap in the study of globalization, covering diverse topics such as business administration, sustainability, corporate social responsibility, finance, accounting, tourism and business informatics.